Response ofsugarcane (Saccharum officinarUnl) to direct and residual effect ofsulphur - TIWARI, R J (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 1997-2001 to study the direct effect of sulphur on plant cane and residual effect of sulphur (obtained from the plant cane) on ratoon canes. The treatments were 0, 20, 40, 60 and 80 kg S/ha. The experiInent was laid out in a randomized block design with 4 replications. ’CoJN 86-141’ sugarcane (125 OOOeyebudsfha) was grown from January to December during each year. A Columon dose ofN, Paud Kwas applied@300, 35 and 50.4 kg /ha respectively to both plant and ratoon canes. The results of experiments showed that the sugarcane crop responded significantly to cane yield and sugar yield up to 40 kg Slha. 60 kg S/ha gave significant higher quality ofjuice and Nand K content injuice and uptake. However, 80 kg S/ha gave higher P and S content injuice and uptake and available soil S status.